Alkaloids - Their Importance in Nature and Human Life 2019
DOI: 10.5772/intechopen.82780
|View full text |Cite
|
Sign up to set email alerts
|

Food Glycoalkaloids: Distribution, Structure, Cytotoxicity, Extraction, and Biological Activity

Abstract: Glycoalkaloids (GA), generally occur as plant steroidal glycosides, are secondary metabolites produced in the leaves, flowers, roots, and edible parts including sprouts and skin of the plants of Solanaceae family. Many of the plants in this family have been stable parts of human diets for centuries, and thus, the occurrence of these compounds has been extensively studied mainly due to concerns regarding their toxicity. GAs are produced by plants as a resistance to challenges such as insects and pests but may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 128 publications
0
4
1
Order By: Relevance
“…A previous study [14] found no statistically significant changes to the glycoalkaloid content of whole potatoes after HPP treatment. Since the glycoalkaloids are present on the skin (usually no deeper than 3 mm) [50,51], minimal processing can result in their decrease and the HPP/US could also trigger degradation to aglycone alkaloids, which can explain the contradiction between the findings of the current study and those from previous work.…”
Section: Effect Of Hpp and Hpp/us On Phytochemicalscontrasting
confidence: 99%
“…A previous study [14] found no statistically significant changes to the glycoalkaloid content of whole potatoes after HPP treatment. Since the glycoalkaloids are present on the skin (usually no deeper than 3 mm) [50,51], minimal processing can result in their decrease and the HPP/US could also trigger degradation to aglycone alkaloids, which can explain the contradiction between the findings of the current study and those from previous work.…”
Section: Effect Of Hpp and Hpp/us On Phytochemicalscontrasting
confidence: 99%
“…Studies have shown that glycoalkaloids are involved in the regulation of plant growth and development, including the formation of roots, shoots, and leaves. They have also been reported to have antioxidant properties, which can help protect plants from oxidative stress caused by environmental factors, such as UV radiation [19,20].…”
Section: Biological Activitymentioning
confidence: 99%
“…Potatoes ( Solanum tuberosum ), contains ( α -solanine and α -chaconine), tomatoes ( Solanum lycopersicum ) ( α -tomatine), eggplants ( Solanum melongena ) ( α -solamargine), and aubergines ( Solanum melongena ) are all members of the Solanaceae family known to produce significant amounts of glycoakaloids [ 5 ]. The toxin is particularly produced in the roots, leaves, flowers, and edible parts of plants, including sprouts and skin [ 66 – 68 ]. Figure 3 shows the potato.…”
Section: Naturally Occurring Plant Food Toxicantsmentioning
confidence: 99%